A Book Working : Six Books by Six Artists (Toronto : A Space, 1980)
Six books included are Journeys of J: The Pegmatite Dikes by Percival; The Real Glasses I Wear by Patton; Sleight of Hand by DeCoster; Postal Workers on Graph Paper Cupw by Duquette; Audience Arrangements by Barber; and The Woman that no one Could Really See by Dunn. With an afterword by Paul Collins.
Engels
boek
Keywords: Percival, Jo; Patton, Andy; DeCoster, Miles; Duquette, Michael; Barber, Bruce; Dunn, James